Investigating the impact of young parents’ demography on child wellbeing for sustainable development of good health and wellbeing - Ting, Tin Tin; New, Yee Hao; Kok, Joey Yen Ni; Wong, Mavis Weng Cheng; Chuah, Shee Yeap; Chaw, Jun Kit; Ali Aitizaz; Lee, Kuok Tiung (The Elite Scientific Forum, Pakistan, 2023)
The importance of children's well-being to realize their potential is a hot topic that ignites intense focus in all societies, including parents, healthcare related scientists, and researchers related to health care. Although there are many studies related to physiological and mental health to promote children's health development, they might not be impactful due to the rapid change in modern living styles these days. This study examines eight demographic factors in detail: background, lifestyle, social and emotional skills, education, marriage, financial status, criminal history, and health, among young parents that could contribute to developing their children's health. Big data analysis is the novelty of this study, which cleaned and transformed the ICPSR big data set (42 data sets with more than 90,000 records), resulting in a 1323 sample size and 231 variables as input into the correlation analysis using SPSS. The result shows the detailed variables of each predictor that influence the health of young adults. Other researchers can use these results to explore more evidence-based solutions to comprehensively monitor the health of current and future generations by clarifying the root causes and effects of demography, as they are the most critical point of influence for their children.